Esophageal temperature management during cryoballoon ablation for atrial fibrillation. (6th November 2022) - Sink, Joshua; Nimmagadda, Kiran; Zhao, Manyun; Andrei, Adin‐Cristian; Gay, Hawkins; Kaplan, Rachel M.; Gao, Xu; Pfenniger, Anna; Patil, Kaustubha D.; Arora, Rishi; Kim, Susan S.; Chicos, Alexandru B.; et al.
Abstract: Introduction: Esophageal thermal injury (ETI) is a well‐recognized complication of atrial fibrillation (AF) ablation. Previous studies have demonstrated that direct esophageal cooling reduces ETI during radiofrequency AF ablation. The purpose of this study was to evaluate the use of an esophageal warming device to prevent ETI during cryoballoon ablation (CBA) for AF. Methods: This prospective, double‐blinded study enrolled 42 patients with symptomatic AF undergoing CBA. Patients were randomized to the treatment group with esophageal warming (42°C) using recirculated water through a multilumen, silicone tube inserted into the esophagus (EnsoETM®; Attune Medical) (WRM) or the control group with a luminal single‐electrode esophageal temperature monitoring probe (LET). Patients underwent upper endoscopy esophagogastroduodenoscopy (EGD) the following day. ETI was classified into four grades. Results: Baseline patient characteristics were similar between groups. Procedural characteristics including number of freezes, total freeze time, early freeze terminations, coldest balloon temperature, procedure duration, posterior wall ablation, and proton pump inhibitor and transesophageal echocardiogram use before procedure were not different between groups. The EGD was completed in 40/42 patients. There was significantly more ETI in the WRM group compared to the LET group ( n  = 8 [38%] vs. n  = 1 [5%], p  = 0.02). All ETI lesions were grade 1 (erythema) or 2 (superficial ulceration). Total freeze time in the left inferior pulmonary vein was predictive of ETI (360 vs. 300 s, p  = 0.03). Conclusion: Use of a luminal heat exchange tube for esophageal warming during CBA for AF was paradoxically associated with a higher risk of ETI.